Nietzsche as critic of Wagner. Prolegomena of the transformation of art into spectacle - Cruz León, Francisco (Pensamiento. Revista de Investigación e Información Filosófica, 2024)
This essay follows Nietzsche’s criticism on Wagner through to three steps. First, I acknowledge the Young philosopher’s admiration for Wagnerian opera considered as a rebirth of ancient musical drama. Second, I explore his progressive disappointment in the light of Schopenhauer’s influence on Wagner. Finally, the essay focuses on Nietzsche’s mature criticism on Wagner noting the XIXth century prolegomena of the general transformation of art into spectacle in a contemporary sense.
Keywords: tragedy; opera; music; metaphysics; spectacle